1967
DOI: 10.1016/0005-2736(67)90003-x
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer interactions of phospholipids and cholesterol

Abstract: SUMMARYI. The force-area characteristics of monolayers of saturated and unsaturated phospholipids have been studied.2. Interaction in phospholipid monolayers depends on the nature of the fatty acid constituents of the phospholipid, and on the temperature.3. The mean area per molecule in mixed films of cholesterol with (I,2-distearoyl)-3-lecithin and (I,2-didecanoyl)-3-1ecithin at 22 ° practically followed the simple additivity rule.4-A condensing effect of cholesterol was evident with films of (I-stearoyl-2-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
0
2

Year Published

1967
1967
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 304 publications
(111 citation statements)
references
References 12 publications
7
102
0
2
Order By: Relevance
“…A strong condensing effect is demonstrated, plotting the mole fraction of sterol against the mean molecular area, and a strong deviation from ideal behaviour is found at all surface pressures. At 50 mol% cholesteryl methyl ether and a surface pressure of 5 or 20 mN • ml 1, the reduction in mean molecular area is 10.5 and 9.5 A2.mol-l, respectively (Table II), which is slightly less than obtained for cholesterol in a mixed film with oleoylstearoylphosphatidylcholine [1,14].…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…A strong condensing effect is demonstrated, plotting the mole fraction of sterol against the mean molecular area, and a strong deviation from ideal behaviour is found at all surface pressures. At 50 mol% cholesteryl methyl ether and a surface pressure of 5 or 20 mN • ml 1, the reduction in mean molecular area is 10.5 and 9.5 A2.mol-l, respectively (Table II), which is slightly less than obtained for cholesterol in a mixed film with oleoylstearoylphosphatidylcholine [1,14].…”
Section: Resultsmentioning
confidence: 82%
“…Many studies have demonstrated that sterols greatly affect the barrier properties of membranes. Monolayer studies have demonstrated a so-called condensing effect [1][2][3], this is a decrease in mean molecular area in mixtures of phospholipid and cholesterol. The increase in chain order in the liquid-crystalline state leads to a decreased permeability [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…A high cholesterol-phospholipids molar ratio of about 0.8 is found in rat erythrocytes [ 17] and unpublished results}. It is known that cholesterol interacts with erythrocyte phospholipids reducing its molecular area [ 18,19]. Electron spin resonance studies indicate that these interactions cause a diminution in the local fluidity of the lipid matrix of the erythrocyte membrane [2].…”
Section: Discussionmentioning
confidence: 81%
“…The pressure-area curves of dilauroyl lecithin, diundecyloyl lecithin dinonanoyl lecithin and dioctanoyl lecithin, as well as dimyristoyl lecithin and didecanoyl lecithin (reproduced from ref. 8), are shown in Fig. 2.…”
Section: Interaction Between Cholesterol and Lecithins Measured Accormentioning
confidence: 99%